Studi Komparatif Multinomial NaÃ¯ve Bayes, Decision Tree, dan K-Nearest Neighbor dalam Klasifikasi Validasi Ulasan Clash of Clans oleh Pengguna Ahli - Ramadhani, Ramadhani; Ramadhanu, Ramadhanu; Ridwan, Mohammad; Abdillah, Amrullah Fajri Artha; Hidayat, Taufik (Jurusan Informatika Universitas Tanjungpura, 2024)
User reviews of the app, including popular games like Clash of Clans, are an important indicator of the quality of the app. However, fake reviews can mislead users and damage the app's reputation. This study aims to classify Clash of Clans reviews on the Google Play Store as